Pharmacokinetic, pharmacodynamic, and behavioural studies of deschloroketamine in Wistar rats - Štefková-Mazochová, Kristýna; Danda, Hynek; Dehaen, Wim; Jurásek, Bronislav; Šíchová, Klára; Pinterová-Leca, Nikola; Mazoch, Vladimír; Krausová, Barbora Hrčka; Kysilov, Bohdan; Smejkalová, Tereza; Vyklický, Ladislav; Kohout, Michal; et al. (British journal of pharmacology, 2022)
BACKGROUND AND PURPOSE: Deschloroketamine (DCK), a structural analogue of ketamine, has recently emerged on the illicit drug market as a recreational drug with a modestly long duration of action. Despite it being widely used by recreational users, no systematic research on its effects has been performed to date. EXPERIMENTAL APPROACH: Pharmacokinetics, acute effects, and addictive potential in a series of behavioural tests in Wistar rats were performed following subcutaneous (s.c.) administration of DCK (5, 10, and 30 mg·kg-1 ) and its enantiomers S-DCK (10 mg·kg-1 ) and R-DCK (10 mg·kg-1 ). Additionally, activity at human N-methyl-d-aspartate (NMDA) receptors was also evaluated. KEY RESULTS: DCK rapidly crossed the blood brain barrier, with maximum brain levels achieved at 30 min and remaining high at 2 h after administration. Its antagonist activity at NMDA receptors is comparable to that of ketamine with S-DCK being more potent. DCK had stimulatory effects on locomotion, induced place preference, and robustly disrupted PPI. Locomotor stimulant effects tended to disappear more quickly than disruptive effects on PPI. S-DCK had more pronounced stimulatory properties than its R-enantiomer. However, the potency in disrupting PPI was comparable in both enantiomers. CONCLUSION AND IMPLICATIONS: DCK showed similar behavioural and addictive profiles and pharmacodynamics to ketamine, with S-DCK being in general more active. It has a slightly slower pharmacokinetic profile than ketamine, which is consistent with its reported longer duration of action. These findings have implications and significance for understanding the risks associated with illicit use of DCK.
Keywords: chování zvířat; Behavior, Animal; krysa rodu Rattus; Rats, Wistar; receptory N-methyl-D-aspartátu; Animals; Receptors, N-Methyl-D-Aspartate; Ketamine; Rats; Illicit Drugs; potkani Wistar; Locomotion; lokomoce; zvířata; zakázané drogy; ketamin